Sinergi Motif Politik dan Motif Normatif dalam Diplomasi Kemanusiaan Tiongkok Pada Masa Pandemi Covid-19 - Rizka Fiani Prabaningtyas; Atin Prabandari (Pusat Penelitian Politik, 2020)
This article seeks to map the patterns of humanitarian diplomacy carried out by China as emerging power in responding to the COVID-19 pandemic. Departing from the debate about political motives in the humanitarian diplomacy strategy carried out by the states, it is increasingly relevant and crucial to examine how humanitarian action, which should be a solution in a crisis situation such as a pandemic, can actually be exploited to serve political interests and how the state humanitarian diplomacy can affect the whole performance of international humanitarian system. The focus on China as a developing country as well as a non-Western donor country (emerging donors) in the international humanitarian aid regime is expected to provide an alternative perspective in seeing the dynamics of actors in the regime. It will be argued that in the context of efforts against COVID-19, Chinaâ€™s humanitarian diplomacy is a mixture of normative and political motives to serve three main national interests, namely normative obligation, stigma management to defend international reputation, and domestic legitimacy of national government. These interests cannot be separated from its status as emerging power trying to fit in the established international humanitarian system while defending its eligibility as influential power in global politics.Â Penelitian ini berupaya untuk memetakan pola pelaksanaan diplomasi kemanusiaan yang dilakukan oleh negara emerging powers dalam merespon pandemi COVID-19. Berangkat dari perdebatan tentang motif politik dalam strategi diplomasi kemanusiaan yang dilakukan oleh negara selama ini, penelitian ini menjadi semakin relevan dan krusial untuk dilakukan untuk mengetahui bagaimana aksi kemanusiaan yang seharusnya menjadi solusi di tengah situasi krisis semacam pandemi dapat dimanfaatkan untuk memenuhi kepentingan politik negara. Selain itu, fokus terhadap Tiongkok sebagai negara berkembang sekaligus negara donor non-Barat (emerging donors) dalam rezim bantuan kemanusiaan internasional diharapkan dapat memberikan pandangan alternatif dalam melihat dinamika karakteristik aktor dalam rezim tersebut. Argumen utama yang dibangun adalah diplomasi kemanusiaan Tiongkok dalam konteks memerangi pandemic COVID-19 adalah perpaduan antara motif normative dan politik untuk memenuhi tiga kepentigan utama, yakni obligasi normative, manajemen stigma untuk mempertahankan reputasi internasional dan legitimasi domestik dari pemerintah pusat. Kepentingan-kepentingan ini tidak dapat dilepaskan dari status dan posisi Tiongkok sebagai emerging power yang harus beradaptasi dan beroperasi di dalam sistem kemanusiaan internasional sekaligus berjuang menjaga eligibilitasnya sebagai negara berpengaruh di dunia.